The social reproduction of difference: Mental illness and the intensive care environment - Floraidh Corfee; Leonie Cox; Carol Windsor (University of Ottawa, 2020)
This paper uses social constructionism to critically explore the social world of intensive care units, and to consider how the presence of mental health consumers impacts on nursing practice. Following a series of interviews with intensive care nurses, our analysis suggested consumers are disenfranchised through stigma, policing, and inattention to psychosocial needs. We argue that the maintenance of knowledge and power networks are fundamental aspects of reality maintenance in intensive care. The social reproduction of typifi cations among nurses about consumers positioned these patients as disrupting the proper business of intensive care units; a process that we argue is bound up with the imbalanced power relationships. Further, intensive care staff maintain power structures serving intensive care interests, such as physiological rescue and the preservation of biomedical authority. We conclude that the production and reproduction of intensive care nursing knowledge maintains a social-power structure at odds with the needs of consumers.